2017
DOI: 10.3168/jds.2016-11263
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the dose and viability of Saccharomyces cerevisiae. 1. Diversity of ruminal microbes as analyzed by Illumina MiSeq sequencing and quantitative PCR

Abstract: This study was conducted to examine effects of the dose and viability of supplemental Saccharomyces cerevisiae on the ruminal fermentation and bacteria population and the performance of lactating dairy cows. Four ruminally cannulated lactating cows averaging 284±18d in milk were assigned to 4 treatments arranged in a 4×4 Latin square design with four 21-d periods. Cows were fed a total mixed ration containing 41.7% corn silage, 12.1% brewer's grains, and 46.2% concentrate on a dry matter basis. The diet was su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
49
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 51 publications
(69 reference statements)
9
49
1
Order By: Relevance
“…In contrast, Ruminococcaceae-NK4A214-group, Ruminococcus 2 , Lachnospiraceae-BS11-gut-group and [Eubacterium]-coprostanoligenes-group were significantly different between the two groups, with higher abundances in the HY group than in the LY group. Jiang et al [42] reported that the increase in the relative abundance of Ruminococcus partly explains why adding live yeast to the diet increases the in vivo digestibility of DM and NDF and the performance of cows. This result illustrates that high-performance cows have higher abundances of Ruminococcus in the rumen fluid, which is consistent with the present research results.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Ruminococcaceae-NK4A214-group, Ruminococcus 2 , Lachnospiraceae-BS11-gut-group and [Eubacterium]-coprostanoligenes-group were significantly different between the two groups, with higher abundances in the HY group than in the LY group. Jiang et al [42] reported that the increase in the relative abundance of Ruminococcus partly explains why adding live yeast to the diet increases the in vivo digestibility of DM and NDF and the performance of cows. This result illustrates that high-performance cows have higher abundances of Ruminococcus in the rumen fluid, which is consistent with the present research results.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteroidales has been reported to be more abundant in high-forage than in low-forage diets and it has been associated with fiber digestion (Henderson et al, 2015) and biohydrogenation of fatty acids in the rumen (Castro-Carrera et al, 2014). Members of the Lachnospiraceae family are gram-positive anaerobic rod-shaped bacteria that mainly ferment pectin (Cotta and Forster, 2016) and are present in the rumen of lactating cows in relative low proportions (Jiang et al, 2017b). Contrary to the results herein, Jiang et al (2017b) reported that lactating dairy cows at the end of their lactation supplemented with live Saccharomyces cerevisiae experienced a decrease in relative abundances of Lachnospiraceae, whereas in the current study Saccharomyces cerevisiae supplementation resulted in an increase in relative abundances of Lachnospiraceae before calving and had Chao (1984).…”
Section: Rumen Microbiotamentioning
confidence: 99%
“…It is well established that the type and amount of forage and concentrate that cows consume influence the rumen microbial composition (Nagaraja and Titgemeyer, 2007;Fernando et al, 2010), rumen microbial activity (Bach et al, 1999), and overall rumen environment. On the other hand, supplementing dairy rations with live yeast has been reported to induce changes in rumen pH, microbial population, and fiber fermentation (Chaucheyras-Durand et al, 2008;Terré et al, 2015;Jiang et al, 2017b), and supplementing live yeast during the transition period could represent an effective strategy to prevent rumen dysfunctions after calving (Jouany, 2006). Therefore, it is likely that live yeast supplementation may exert some effects on the rumen by altering the microbiota, the ruminal environment, or both.…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, YC supplementation increased the PUFA content and decreased the SFA and MUFA content. The synthesis of microbial fatty acids is affected by the ruminal environment (Turner et al, ), which might be influenced by YC supplementation (Jiang et al, ; Mohamed et al, ) and/or its interaction with dietary compositions (Liu et al, ). These may also be the reasons why the concentrations of SFA, MUFA and PUFA were affected by the dietary NSCFR × supplemental YC level interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Yeast culture (YC) can modulate rumen fermentation functions (Mohamed, Maareck, Abdel-Magid, & Awadalla, 2009), stimulate bacterial metabolism activity (Jiang et al, 2016;Liu et al, 2019;Mullins et al, 2013;Nisbet & Martin, 1991), increase synthesis of microbial protein and promote utilization of fermentation products (Miller-Webster, Hoover, Holt, & Nocek, 2002;Moallem, Lehrer, Livshitz, Zachut, & Yakoby, 2009;Robinson & Erasmus, 2009). Therefore, YC products have been wildly studied for decades as a modifier of ruminant nutrition.…”
Section: Introductionmentioning
confidence: 99%